ANALISIS PERSEPSI KONSUMEN TERHADAP PRODUK BABI GULING DI KABUPATEN BADUNG - B. K. P. Mat; B. R. T. Putri; N. W. T. Inggriati (Fakultas Peternakan Universitas Udayana, 2025)
Consumer perception is the stage where a person selects, determines, and interprets information to produce a meaningful description of a product, in the context of traditional food, this perception includes taste, appearance, and cultural values ​​​​inherent in the food. The purpose of this study is to determine consumer perceptions of quality, taste, appearance, price, service and environmental cleanliness in roast pork restaurants in Badung Regency. The study was conducted for 2 months in five roast pork restaurants in Badung Regency. The research respondents were consumers of roast pork restaurants selected by purposive sampling of 75 people, with a quota of 15 people for each restaurant, the methods used were quantitative and qualitative methods. The study findings indicate that product quality obtained a mean score of 4.22 which is classified as good, product taste produced a mean score of 4.35 with a very good classification, appearance obtained a mean score of 4.30 which is classified as very good, price obtained an average score of 3.97, location produced a mean score of 4.20 which is classified as good, service obtained a score of 4.10 which is classified as good, and environmental cleanliness obtained a mean score of 4.25 which is classified as very good. According to the research findings, it was concluded that consumers were very satisfied with the quality, taste, appearance, price, location, service, and environmental cleanliness. ABSTRAK Persepsi konsumen merupakan tahapan yang mana seseorang memilih, menetapkan, serta menginterpretasikan informasi agar menghasilkan deskripsi yang berarti tentang suatu produk, dalam konteks makanan tradisional, persepsi ini meliputi rasa, tampilan, dan nilai budaya yang melekat pada makanan tersebut. Tujuan penelitian mengetahui persepsi konsumen terhadap kualitas, citarasa, tampilan, harga, pelayanan dan kebersihan lingkugan di rumah makan babi guling di kabupaten Badung. Penelitian dilakukan selama 2 bulan di lima warung babi guling di Kabupaten Badung. Responden penelitian adalah konsumen warung babi guling yang di pilih secara purposive sampling sebanyak 75 orang, dengan quota masing- masing rumah makan sebanyak 15 orang, metode yang di gunakana metode kuantitatif serta kualitatif. Temuan studi mengindikasikan jika kualitas produk memperoleh skor mean 4,22 yang tergolong klasifikasi baik, citarasa produk menghasilkan skor mean skor 4,35 dengan klasifikasi sangat baik, tampilan mendapatkan skor mean 4,30 yang tergolong klasifikasi sangat baik, harga memperoleh nilai rata-rata 3,97, lokasi menghasilkan skor mean 4,20 masuk klasifikasi baik, pelayanan mendapatkan skor 4,10 masuk kategori baik, dan kebersihan lingkungan mendapatkan skor mean 4,25 yang masuk klasifikasi sangat baik. Menurut temuan penelitian disimpulkan bahwa konsumen sangat puas terhadap kualitas, citarasa, tampilan, harga, lokasi, pelayanan, dan kebersihan lingkungan.